2016
DOI: 10.1016/j.molcel.2016.03.032
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of DNA Translocation Efficiency within the Chromatin Remodeler RSC/Sth1 Potentiates Nucleosome Sliding and Ejection

Abstract: SUMMARY The RSC chromatin remodeler slides and ejects nucleosomes, utilizing a catalytic subunit (Sth1) with DNA translocation activity, which can pump DNA around the nucleosome. A central question is whether and how DNA translocation is regulated to achieve sliding versus ejection. Here, we report the regulation of DNA translocation efficiency by two domains residing on Sth1 (Post-HSA and Protrusion 1), and by actin-related proteins (ARPs) which bind Sth1. ARPs facilitated sliding and ejection by improving ‘c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
118
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(126 citation statements)
references
References 32 publications
7
118
1
Order By: Relevance
“…However, unlike with SNF2h, the dCX double cross-links do not inhibit nucleosome sliding by RSC but instead greatly increase octamer eviction. A recent RSC study has suggested that faster DNA translocation correlates with higher levels of octamer eviction, while slower translocation favors nucleosome sliding (52). Our results suggest that partitioning between sliding and eviction is further regulated by the distortability of the histone octamer.…”
Section: Discussionmentioning
confidence: 99%
“…However, unlike with SNF2h, the dCX double cross-links do not inhibit nucleosome sliding by RSC but instead greatly increase octamer eviction. A recent RSC study has suggested that faster DNA translocation correlates with higher levels of octamer eviction, while slower translocation favors nucleosome sliding (52). Our results suggest that partitioning between sliding and eviction is further regulated by the distortability of the histone octamer.…”
Section: Discussionmentioning
confidence: 99%
“…As sfh1-13 alone did not induce Tf2 RNA, we speculate that Sfh1/RSC partly contribute to HIRA-dependent repression and in the absence of Sfh1/ RSC, Abp1 and partly active HIRA pathway cooperatively repress Tf2 transcription. RSC has been shown to function in eviction of nucleosome in vitro (Clapier et al, 2016;Sinha et al, 2017) and linked with active transcription because of its active role for formation of NDR at TSS (Badis et al, 2008;Hartley & Madhani, 2009;Parnell et al, 2008;Wippo et al, 2011;Yague-Sanz et al, 2017). In contrast, budding yeast RSC localizes at the histone HTA1/HTB promoter via corepressor complex containing HIRA and plays a role in redundant repression mechanisms (Ng, Robert, Young, & Struhl, 2002).…”
Section: Sfh1 Contributes To Repression Of Retrotransposons In Paramentioning
confidence: 99%
“…In addition, RSC contributes to generates nucleosome-depleted region (NDR), especially around transcription start sites in both yeasts (Badis et al, 2008;Hartley & Madhani, 2009;Parnell et al, 2008;Wippo et al, 2011;Yague-Sanz et al, 2017). Therefore, budding yeast RSC is shown to have nucleosome sliding and eviction activity in vitro (Clapier et al, 2016;Sinha et al, 2017). At fission yeast centromeric heterochromatin, histone deacetylase complex (HDAC) Clr3/SHREC eliminates NDR formation at particular site by antagonizing RSC.…”
Section: Introductionmentioning
confidence: 99%
“…The "ARP module", which consists of Arp7, Arp9, and the fungal-specific protein Rtt102, binds to the HSA domain in Sth1, a helical segment N-terminal to the ATPase domain [15][16][17] . Binding of the ARP module lowers the intrinsic rate of ATPase turnover of Sth1, yet paradoxically increases remodeling rates, suggesting that ARP binding acts to convert ATP turnover by the core ATPase into productive remodelling events 18 . Additionally, two other SWI/SNF-specific domains, the post-HSA and Protrusion (P1), seem to interact both physically 17,19 and genetically 15 with the HSA domain, indicating that they act as a regulatory hub to control ATPase turnover and remodelling 18 .…”
Section: Introductionmentioning
confidence: 99%